Epidural spinal cord stimulation improves motor function in rats with chemically induced parkinsonism - Zhong, Hui (Neurorehabil Neural Repair, 2019)
BACKGROUND. Epidural stimulation of the spinal cord can reorganize and change the excitability of the neural circuitry to facilitate stepping in rats with a complete spinal cord injury. Parkinson’s Disease (PD) results in abnormal supraspinal signals from the brain to the spinal cord that affect the functional capacity of the spinal networks. OBJECTIVE. The objective was to determine whether epidural stimulation (electrical enabling motor control, eEmc) of the lumbosacral spinal cord can reorganize the spinal networks to facilitate hindlimb stepping of rats with parkinsonism. METHODS. A unilateral 6-OHDA lesion of the nigrostriatal pathway was used to induce parkinsonism. Sham rats (N=4) were injected in the same region with 0.1% of ascorbic acid. Stimulation electrodes were implanted epidurally at the L2 and S1 (N=5) or L2 (N=5) spinal levels. RESULTS. The 6-OHDA rats showed severe parkinsonism in cylinder and adjusting step tests, and were unable to initiate stepping when placed in a running wheel and dragged their toes on the affected side during treadmill stepping. During eEmc, the 6-OHDA rats initiated stepping in the running wheel and demonstrated improved stepping quality. CONCLUSION. Stepping was facilitated in rats with parkinsonism with spinal cord stimulation. The underlying assumption is that the normal functional capacity of spinal networks is affected by supraspinal pathology associated with PD which either generates insufficient or abnormal descending input to spinal networks and that eEmc can appropriately modulate spinal and supraspinal networks to improve the motor deficits.